Districts Naming in Medan: An Anthropolinguistics Study - Narhan, Raees; Solehatun, Prima; Lubis, Tasnim (Tradition and Modernity of Humanity, 2023)
The background of the naming of kelurahan in two sub-districts in Medan, North Sumatra in areas that have links with culture, language and cognition. This study aims to find out the origins of village names in two sub-districts in Medan, North Sumatra by finding reasons and connections between culture, language and thoughts that reflect street names in these sub-districts. The naming of kelurahan in two sub-districts in Medan, North Sumatra can be categorized based on their basic shape, the morphological process that led to their formation, and their significance. The subjects of this research were the villages of Asam Kumbang, Sunggal, and Kampung Lalang villages. Data collection was carried out by conducting interviews and interviews in regional sub-districts, patriarchs of Datuk Badiuzzaman descent and in the surrounding community and advanced techniques, namely all-cause techniques, recording techniques, and note-taking techniques. The approach used in this study is an anthropolinguistic approach and is examined in a qualitative descriptive manner with an informal data presentation method used to process and present the expected data.